z+(-6)-2=-10

Simple and best practice solution for z+(-6)-2=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z+(-6)-2=-10 equation:


z+(-6)-2=-10

We simplify the equation to the form, which is simple to understand
z+(-6)-2=-10

Remove unnecessary parentheses
+z-6-2=-10

We move all terms containing z to the left and all other terms to the right.
+1z=-10+6+2

We simplify left and right side of the equation.
+1z=-2

We divide both sides of the equation by 1 to get z.
z=-2

See similar equations:

| 5x+3i=15+yi | | (3z^(1/5))^4 | | G-0.28g-0.09g=749.7 | | 7p-50p=-7 | | 7.6x+15.2y=38 | | 2(3x+2)=1/2(10x+16) | | (3z^1/5)^4 | | 25=31.25 | | G-0.28g-0.09=749.7 | | 31-2(3+7)= | | 15y+20=4 | | (14)-(4)= | | 2m+3m=7 | | 12x+18y=15 | | 2.75y-6=10 | | r/43=-8 | | -7(x+2)=-10 | | 36.90p=9 | | a/21/23=-3.5 | | 6+7x-2=6x+34-4x | | -13=-4x-8+3 | | 9.3n+8.2=54.7 | | 1/6*8/10 | | 9+13p-7=8p+11-4p | | 12/y | | 23/4y-6=10 | | -2(2m-5)-3m=59 | | 17p+q-7p+19q= | | w/2.8=4-2 | | 2+8-9x=3/1 | | 4(4x-7)=16x-28 | | 7-6a+5a=3a-5a |

Equations solver categories